Effect of α-galactosidase Supplementation in Diet on Egg Production, Egg Quality and Dietary Digestibility of Laying Hens - Harnkaew, Chonladda; Bunchasak, Chaiyapoom; Rakangthong, Choawit; Sukontasing, Sirapan; Poeikhampha , Theerawit (International Journal of Poultry Science, 2018)
Background and Objective: The carbohydrates in soybean meal consist of approximately 10% oligosaccharides and are linked by an α-1,6 galactosidase bond which cannot be broken down in the small intestine of monogastric animals due to the absence of endogenous α-1,6 galactosidase. This experiment was conducted to determine the effect of α-galactosidase supplementation in the laying hen diet on egg performance, egg quality and dietary digestibility. Methodology: A total of 576 Lohmann brown-classic hens (28 weeks old) were divided into 3 groups of 8 replications with 24 hens each. This experiment design was completely randomized design and there were 3 experimental diets, (1) Positive control diet, (2) Positive control diet decreased by 88 kcal kg–1 ME and supplemented with α-galactosidase at 0.022 and (3) Positive control decreased by 88 kcal kg–1 ME without any supplementation of α-galactosidase (negative control). Results: At the end of the 16 weeks of feeding trial, using α-galactosidase significantly improved egg production (p